With the Booming of Xi’an, the Opportunities and Challenges Facing the Economic Development of Northwest China - Feng, Boyue (International Journal of Global Economics and Management, 2024)
In recent years, Xi’an, a city with a long history, has been successfully promoted to the only new first-tier city in Northwest China. Its explosive fire has made other regions in Northwest China see the hope of a substantial rise in economic development. With the popularity of Xi’an undoubtedly plays a leading role in the economic development of Northwest China. Therefore, in order to make the economic development of other provinces in Northwest China also have a qualitative leap, we must first find out the reasons for the bomming of Xi’an and the inspiration behind the reasons as samples, and then analyze the development potential and local characteristics of the other four provinces in Northwest China. Consider whether the development of these provinces can completely follow the economic development route of Xi’an, and finally consider the problems and challenges that each province may face.